2019
DOI: 10.1371/journal.pone.0223748
|View full text |Cite
|
Sign up to set email alerts
|

Expanded consumer niche widths may signal an early response to spatial protection

Abstract: Marine management interventions are increasingly being implemented with the explicit goal of rebuilding ocean ecosystems, but early responses may begin with alterations in ecological interactions preceding detectable changes in population-level characteristics. To establish a baseline from which to monitor the effects of spatial protection on reef fish trophic ecology and track future ecosystem-level changes, we quantified temperate reef fish densities, size, biomass, diets and isotopic signatures at nine site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Second, developing tailored spatial-specific fishing strategies that account for both residency and potential sources of black rockfish contributes significantly to local fishery sustainability. Owing to the limited space and food availability in the reef areas, a high assemblage of individuals can lead to intraspecific competition for refuge and food resources [59,60]. By considering the diverse potential sources of black rockfish, implementing a spatial-specific fishing strategy with distinct quotas can help alleviate intraspecific competition within the reef area and foster a sustainable level of exploitation in coastal regions [61].…”
Section: Implications For Stock Enhancement Managementmentioning
confidence: 99%
“…Second, developing tailored spatial-specific fishing strategies that account for both residency and potential sources of black rockfish contributes significantly to local fishery sustainability. Owing to the limited space and food availability in the reef areas, a high assemblage of individuals can lead to intraspecific competition for refuge and food resources [59,60]. By considering the diverse potential sources of black rockfish, implementing a spatial-specific fishing strategy with distinct quotas can help alleviate intraspecific competition within the reef area and foster a sustainable level of exploitation in coastal regions [61].…”
Section: Implications For Stock Enhancement Managementmentioning
confidence: 99%
“…Long‐term research in California indicates that spatial protections can help rebuild the densities and body sizes of rockfish and of lingcod ( Ophiodon elongatus : a co‐occurring, highly mobile, fished species) (Caselle et al, 2015; Keller et al, 2019; Starr et al, 2015; Thompson et al, 2017). Also, research within the NSB points to differences between protected and fished areas in the trophic structure of rockfishes and lingcod (Olson et al, 2019). MPA benefits for rockfish, however, may require many years to accrue and the required time may vary between species and locations (McGreer et al, 2020; Starr et al, 2015).…”
Section: Examples Of Species Declinesmentioning
confidence: 99%
“…For some species, however, declines in size and age structure have continued and their biomass remains depressed and references within). RCAs can help reverse these trends, yet prior studies in British Columbia, conducted only 5-7 years after RCA implementation, found no evidence of larger or more abundant rockfishes inside protected sites (Haggarty, Shurin & Yamanaka, 2016;Olson, Trebilco & Salomon, 2019). As time since RCA implementation progresses, size and biomass increases are more likely to be detected (Starr et al, 2015;Keller et al, 2019), particularly for shorter-lived species with greater k values (Kaplan et al, 2019).…”
Section: Introductionmentioning
confidence: 97%